Strain dependent effects of conditioned fear in adult C57Bl/6 and Balb/C mice following postnatal exposure to chlorpyrifos: Relation to expression of brain acetylcholinesterase mRNA - Oriel, Sarit; Kofman, Ora (Frontiers in Behavioral Neuroscience, 2015)
Following reports of emotional psychopathology in children and adults exposed to organophosphates, the effects of postnatal chlorpyrifos (CPF) on fear conditioning and depression-like behaviors were tested in adult mice. Concomitant changes in expression of mRNA for synaptic and soluble splice variants of acetylcholinesterase (AChE) were examined in mouse pups and adults of the Balb/C and C57Bl/6 (B6) strains, which differ in their behavioral and hormonal stress response. Mice were injected subcutaneously with 1 mg/kg CPF on postnatal days 4-10 and tested as adults for conditioned fear, sucrose preference and forced swim. Acetylcholinesterase activity was assessed in the brains of pups on the first and last day of treatment. Expression of soluble and synaptic AChE mRNA was assessed in brains of treated pups and fear-conditioned adults using real-time PCR. Adult Balb/C mice exposed postnatally to CPF showed exacerbated fear conditioning and impaired active avoidance. Adult B6 mice exposed postnatally to CPF showed a more specific fear response to tones and less freezing in the inter-tone intervals, in contrast to the vehicle-pretreated mice. Chlorpyrifos also attenuated sweet preference and enhanced climbing in the forced swim test. Chlorpyrifos-treated mice had increased expression of both synaptic and readthrough AChE transcripts in the hippocampus of Balb/C mice and decreased expression in the amygdala following fear conditioning. In conclusion, postnatal CPF had long-term effects on fear and depression as well as on expression of AChE mRNA. These changes may be related to alteration in the interaction between hippocampus and amygdala in regulating negative emotions.